IMPLEMENTASI NILAI TOLERANSI BERAGAMA ERA MERDEKA BELAJAR DI SMP NEGERI 21 MALANG - Putri Wahyuni; Khoirul Asfiyak; Adi Sudrajat (VICRATINA, 2022)
The implementation of religious tolerance values in the era of independent learning isa challenge that must be passed by teachers and students at the State Junior HighSchool 21 Malang. Focus of the research discuss about the process and results of theimplementation of religious tolerance values. To achieve the objectives of this study,the researcher used a qualitative approach based on phenomenology with the type ofcase study research. Researchers found the results of this study, among others, namelythe implementation process includes planning and implementation consisting ofapproaches, methods, models, techniques, strategies and evaluation of learning. Theresults of this study consisted of three ampek namely cognitive, affective andpsychomotor.